The role of intercultural differences and challenges faced in negotiating active mine sites' rehabilitation objectives from Africa to Europe - Rodolaki, Chrysanthi; Barakos, George; Hitch, Michael (Elsevier, 2023)
Analysing the challenges that govern an active mining project during negotiations, especially its rehabilitation, can give a better insight from a cross-cultural perspective. Despite the cultural variations distinguished by region or country, there can be common strategies in negotiating rehabilitation objectives of mine sites via specific negotiation strategies. This study investigates how intercultural differences influence the rehabilitation of active mine sites from Africa to Europe. The goal is to provide new insights into cultural differences regarding the communication process in negotiations, issue an unprecedented groundwork for research, and contribute to practitioners of cross-cultural business negotiations by better understanding the context. Through semi-structured interviews, primary data was collected from participants representing a multinational mining corporation based in Europe negotiating the rehabilitation of active mine sites in Cameroon and South Africa. The analysis employed a data reduction process, interpreting the collected data, connecting it to existing literature, and analysing the findings. The outcomes showed the significance of cultural dimensions to variables of international business negotiations. They indicated the attention that culturally diverse organisations must pay to them to increase their chances of succeeding in rehabilitating mine sites’ integration. African and European stakeholders demonstrated opposing negotiation styles that affect how they communicate, build their agreements, show their emotions, and are willing to take risks.